Fertility management in Kallmann syndrome: a step towards optimization - Bathwal, Shikha; Sharma, Sunita; Agarwal, Nupur; Chakravarty, Baidyanath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Kallmann syndrome (KS) is a genetic disorder with an incidence of one per 50,000 women. It is associated with hypogonadotropic hypogonadism and anosmia/hyposmia. An important aspect of managing KS is to achieve successful pregnancy. We hereby present a case series of three patients with KS who successfully conceived with human menopausal gonadotropin (HMG) induction. One patient achieved pregnancy with ovulation induction, second with fresh embryo transfer and the third with frozen embryo transfer. Two of these three women delivered at term and both babies were doing well at one year of follow up. Both received cyclical hormone therapy (HT) since adolescence. The third patient received HT only for six months before starting ovulation induction. She conceived twice but miscarried at both occasions. At times, it may be challenging to attain fertility in Kallmann syndrome but with persistent efforts results are usually rewarding. It is important to diagnose KS and start hormone therapy at appropriate time so that satisfactory fertility outcome can be achieved.